Education, school and cultural processes in contemporary Italy - Canales Serrano, Antonio Francisco (Historia y Memoria de la Educación, 2020)
Review of the book by Sani, Roberto. Education, school and cultural processes in contemporary Italy. Macerata: Edizioni Università di Macerata, 2018